Analysing neutron radiation damage in YBa2Cu3O7–x high‐temperature superconductor tapes. (6th January 2022) - Linden, Y.; Iliffe, W.R.; He, G.; Danaie, M.; Fischer, D.X.; Eisterer, M.; Speller, S.C.; Grovenor, C.R.M.
Abstract: Superconducting windings will be necessary in future fusion reactors to generate the strong magnetic fields needed to confine the plasma, and these superconducting materials will inevitably be exposed to neutron damage. It is known that this exposure results in the creation of isolated damage cascades, but the presence of these defects alone is not sufficient to explain the degradation of macroscopic superconducting properties and a quantitative method is needed to assess the subtle lattice damage in between the clusters. We have studied REBCO‐coated conductors irradiated with neutrons to a cumulative dose of 3.3 × 10 22 n/m 2 that show a degradation of both Tc and Jc values, and use HRTEM analysis to show that this irradiation introduces ∼10 nm amorphous collision cascades. In addition, we introduce a new method for the analysis of these images to quantify the degree of lattice disorder in the apparently perfect matrix between these cascades. This method utilises Fast Fourier and Discrete Cosine Transformations of a statistically relevant number of HRTEM images of pristine, neutron‐irradiated and amorphous samples and extracts the degree of randomness in terms of entropy values. Our results show that these entropy values in both mid‐frequency band FFT and DCT domains correlate with the expected level of lattice damage, with the pristine samples having the lowest and the fully amorphous regions the highest entropy values. Our methodology allows us to quantify 'invisible' lattice damage to and correlate these values to the degradation of superconducting properties, and also has relevance for a wider range of applications in the field of electron microscopy where small changes in lattice perfection need to be measured.